1992
DOI: 10.1017/s0031182000074096
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and sensitive detection of Leishmania kinetoplast DNA from spleen and blood samples of kala-azar patients

Abstract: Following sequence analysis of a Leishmania donovani kinetoplast DNA (kDNA) minicircle, we have developed synthetic oligonucleotides for use in the polymerase chain reaction (PCR). With these primers, we have amplified L. donovani kDNA from splenic aspirates and blood samples taken from kala-azar patients. Treatment of the samples for PCR requires only limited DNA purification by lysis in SDS, digestion with proteinase K, phenol extraction and ethanol precipitation of the resulting nucleic acid. We have obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
94
2
1

Year Published

1995
1995
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 176 publications
(101 citation statements)
references
References 13 publications
(9 reference statements)
4
94
2
1
Order By: Relevance
“…However, despite using primers for kDNA targets, Smyth et al (1992) found the same sensitivity (1 pg/µL) reported in the present study. Although most authors have used the kinetoplast minicircle region for primer construction, the present study showed that primers selected from 18S rRNA are a reliable option for specific molecular detection of L. infantum chagasi.…”
Section: Resultssupporting
confidence: 83%
“…However, despite using primers for kDNA targets, Smyth et al (1992) found the same sensitivity (1 pg/µL) reported in the present study. Although most authors have used the kinetoplast minicircle region for primer construction, the present study showed that primers selected from 18S rRNA are a reliable option for specific molecular detection of L. infantum chagasi.…”
Section: Resultssupporting
confidence: 83%
“…Diagnostic methods based on deoxyribonucleic acid (DNA) have, however, now made the sensitive and rapid detection and identification of many microorganisms possible. Over the last couple of decades, for example, assays based on PCR have proved to be sensitive and powerful tools for the detection and identification of Leishmania in clinical samples, without the need to culture the parasites (Rodgers et al, 1990;Smyth et al, 1992;Lopez et al, 1993;Noyes et al, 1998). In the present study, based in Ahvaz (the capital city of Khouzestan), a nested PCR was used to confirm the microscopical diagnosis of CL and identify the causative parasites to species level.…”
mentioning
confidence: 99%
“…Primers specific for L. Viannia kDNA (B1/B2) developed by de Brujin and Barker (1992) and for L. chagasi kDNA (DB8/AJS3) developed by Smyth (1992) were used in these assays. PCR products were hybridized with biotinilated probes.…”
Section: Methodsmentioning
confidence: 99%